Integration processes in science: the role of the theory of synergetics in the emergence of expressive words - Zhonkeshov, Б.С.; Kasen , Е.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article provides an overview of the phenomenon of integration in science, considered as a theoretical basis for solving current problems of linguistics. Based on the works of researchers published so far, the authors seek to answer the following questions: what is meant by the concept of "integration", what is its role in the formation of emotionally expressive vocabulary, and what models generating emotionally expressive meaning arose as a result of the application of the theory of synergetics. The authors try to prove that the emergence of emotionally expressive words occurs as a result of the integration of several disciplines, namely phonetics and semantics, morphology and emotion, imagery and evaluation. In addition, defining the concepts of synergetics (bifurcation, fluctuation, attractor, chaos), it is proposed to consider chaos as a self-organizing system that creates expressive meanings and expressive structures. Using specific examples from the Kazakh language, the authors try to demonstrate that modern emotional-expressive units once represented a chaotic state, eventually transformed from chaos into attractors, and as a result, stable emotional-expressive models were formed in the language. The article is intended for undergraduates and doctoral students interested in linguistics, literature, psychology, philosophy, cognitive science and other scientific fields, as well as researchers working in these fields.